Avaliação do uso de soro para diagnóstico de câncer de mama por meio das técnicas espectroscópicas FTIR E RAMAN - Monteiro, Eva Mendes (2021)
Infrared spectroscopy with attenuated total reflection fourier transforms (ATR-FTIR) and Raman spectroscopy are variant techniques of vibrational spectroscopy, allow rapid and non invasive identification, with high specificity, reagent-free, low cost, reduced volume of samples and simple to operate. These techniques allow obtaining information not only about the chemical particles through the identification of functional groups, but also allow qualitative and quantitative analysis of the chemical substances present in the analyzed material. Both spectral techniques have been used in the diagnosis of several diseases, by detecting small variations in the molecular content related to the disease and indicating the potential of early diagnosis. Breast cancer is the leading cause of death among worldwide women. In 2020, among the most incident cancers in the world, in both sexes and ages, breast cancer ranked first with an estimated 2,261,419 new cases.For each year of the 2020-2022 triennium, an estimated 66,280 new cases are estimated. This value corresponds to an estimated risk of 61,61 new cases per 100 thousand women. The diagnosis of breast cancer comprises four conventional techniques: histopathology, mammography, ultrasound and magnetic resonance. However, the available techniques have their limitations for the early diagnosis of breast cancer, the high cost and no indication for young women. The aim of our study is to analyze comparative spectroscopic techniques in the serum samples of patients withbreast cancer and benign breast disease. We applied the ATR-FTIR tool associated with the linear discriminant analysis (LDA) classifier to identify changes in the serum of patients with malignant tumors and benign breast disease to investigate their potential in the diagnosis of breast cancer. Serum infrared spectrum classification by LDA showed a sensitivity of 89%, specificity of 74% and accuracy of 84% between malignant tumors and benign patients. Raman spectroscopy detected seven spectral bands with potential and, of these, a band in the region of the 1083 cm-1 wavenumber in the second derivative showed a strong correlation, with sensitivity and specificity of 80.00% and 61.1%, respectively, in compared to breast cancer and benign breast disease. We conclude that this study is the first to characterize and use derived chemical analysis. Furthermore, it demonstrated the possible potential use of the spectral biomarker of ATR-FTIR and serological Raman. Thus, ATR-FTIR and Raman spectroscopy are promising and robust techniques for an early diagnosis and differentiate benign breast disease from breast cancer.